Menggambarkan Peran Pendidikan Digital dalam Meningkatkan Kualitas Sumber Daya Manusia di Sektor Ekonomi Kreatif (International Forum of Researchers and Lecturers, 2025)
In the rapidly evolving digital era, human resources (HR) are a key factor in facing global challenges and leveraging technological opportunities. Education plays a strategic role in shaping high-quality human resources that are adaptive, innovative, and competitive. This study explores how education, through the enhancement of digital literacy, 21st-century skills, and the use of information technology, significantly contributes to improving HR quality. The transformation of education—covering technology-based curricula, digital learning methods, and vocational training—has become essential in creating a workforce that is ready to compete in the digital age. The discussion concludes that investment in an education system responsive to technological developments will produce superior and highly competitive human capital. Therefore, collaboration between government, educational institutions, and industry sectors is crucial in creating a relevant and sustainable learning ecosystem.